A hydrocracking catalyst and its preparation method and application
By modifying the hydrogen-type molecular sieve with non-branch aluminum, combining alumina to form a support, and supporting hydrogenated active metal components, the problem of low activity of the existing catalyst is solved and efficient stone brain is achieved Oil production and catalyst selectivity are improved.
Patent Information
- Application Number
- CN202111675951.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-31
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2041-12-31
AI Technical Summary
The activity of existing hydrocracking catalysts is low, resulting in a low yield of naphtha, which is difficult to meet the purpose of refineries to transform existing devices or increase processing volume to achieve the goal of increasing naphtha production.
By modifying the hydrogen-type molecular sieve with non-skeleton aluminum using organic dicarboxylic acid as a dealuminant, a specially modified Y-molecular sieve is obtained, and combined with alumina to form a carrier, and then the hydrogenated active metal component is supported on On the support, an efficient hydrocracking catalyst is formed.
It has achieved efficient naphtha production, improved the cracking activity and selectivity of the catalyst, enhanced the crystallinity and pore passage of the molecular sieve, and met the refinery's demand for naphtha production.
Smart Images

Figure BDA0003451300180000091 
Figure BDA0003451300180000101 
Figure BDA0003451300180000102
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical synthesis, and particularly relates to a hydrocracking catalyst suitable for producing high-aromatic naphtha, and a preparation method and application thereof. Background Art
[0002] In recent years, the demand for refined oil products has gradually diverged, with the demand for automotive diesel entering a negative growth zone and the growth rate of automotive gasoline slowing down. Unlike the refined oil market, the market demand for chemical raw materials such as aromatics is strong and growing at a faster rate year by year. At the same time, as the diesel-to-gasoline ratio of consumption gradually decreases, the outlet of diesel has also attracted much attention.
[0003] Hydrocracking technology has become the best means to produce high-quality clean middle distillates by deep processing of heavy oil with its unique advantages. At present, the activity of catalytic diesel hydrocracking catalyst is not very high, resulting in a low naphtha yield, which makes it difficult for refineries to modify existing equipment or increase processing capacity to further increase naphtha production.
[0004] As a key material of hydrocracking catalyst, the performance of molecular sieve directly affects the reaction performance of hydrocracking catalyst. According to different production needs, molecular sieve can be modified differently to meet the requirements of use. For example, acid treatment modification of molecular sieve is conducive to improving the stability and cracking activity of molecular sieve, and has been widely used for a long time. However, during the acid treatment process, it is inevitable that non-framework aluminum species will be deposited inside the pores, blocking the molecular sieve pores and reducing the utilization and accessibility of the active sites in the molecular sieve crystal. At the same time, it will cause the molecular sieve crystallinity to decrease, which is not conducive to obtaining ultra-stable molecular sieves with low unit cell and high crystallinity. Therefore, how to improve the molecular sieve crystallinity as much as possible while reducing the molecular sieve unit cell has always been a challenging task, which is of great significance to the field of molecular sieve modification technology.
[0005] CN105709801A discloses a method for preparing a chemical raw material hydrocracking catalyst that can produce a lot of naphtha. The naphtha yield can be as high as 50wt%, but the reaction pressure is around 15Mpa and the reaction conditions are relatively harsh.
[0006] CN105709798A discloses a method for preparing a hydrocracking catalyst and its application. The Y molecular sieve used is obtained by hydrothermal ultrastabilization and ammonium fluorosilicate modification, and is used for hydrocracking to increase the production of heavy naphtha, and has high catalytic activity and selectivity.
[0007] CN104229823A discloses a modification method of ultrastable Y molecular sieve (USY). The method is characterized in that an organic acid and an inorganic salt dealuminizing agent are added simultaneously during the modification process to perform a combined modification of an organic acid and an inorganic salt. The mesoporous volume of the USY molecular sieve actually obtained by this method accounts for less than 50% of the total volume, and the crystallinity is less than 85%.
[0008] CN101172260A discloses a method for preparing a hydrocracking catalyst. The catalyst carrier is prepared by introducing a molecular sieve slurry into the amorphous silica-alumina gelling process. The amorphous silica-alumina provides a certain weak acid center to adjust the catalytic activity of the catalyst, thereby achieving the purpose of matching the catalyst activity and selectivity.
[0009] From the application of molecular sieves with acid catalysis in industrial catalytic processes, their performance mainly depends on the following two aspects: selective adsorption and reaction. The total pore volume and mesopore volume of molecular sieves prepared by conventional modification methods are both small, which is not conducive to the conversion of raw material macromolecules. Therefore, modified molecular sieves with open pore structure, high mesopore content and more exposed acid centers can process raw materials with larger molecules and heavier oil products, and show more superior performance in terms of improving the conversion rate of macromolecules, thereby improving the level of catalysts. Summary of the invention
[0010] The object of the present invention is to provide a hydrocracking catalyst capable of effectively achieving high yield of high aromatic potential naphtha and a preparation method thereof.
[0011] In order to achieve the above object, the present invention provides a hydrocracking catalyst, wherein the catalyst comprises a hydrogenation active metal component and a carrier, and the carrier comprises a modified molecular sieve and alumina; wherein,
[0012] The modified molecular sieve is prepared by a method comprising the following steps:
[0013] At 50-120° C., a hydrogen-type molecular sieve having non-framework aluminum is dealuminated using an organic dicarboxylic acid solution; wherein the organic dicarboxylic acid in the organic dicarboxylic acid solution contains a carbon-carbon double bond and two carboxyl groups are arranged on the same side of the carbon-carbon double bond, and the spatial configuration is a cis structure;
[0014] The molecular sieve after dealuminization is washed and dried to obtain a modified molecular sieve.
[0015] In the above-mentioned hydrocracking catalyst, a specially modified molecular sieve is used as a carrier component. This specially modified molecular sieve is obtained by modifying a hydrogen-type molecular sieve with non-framework aluminum using an organic dicarboxylic acid in which two carboxyl groups are in a cis-structure as a dealuminizing agent. This specially modified molecular sieve removes ionic non-framework aluminum with high selectivity, and basically does not contain ionic non-framework aluminum, and its framework aluminum and polymerized non-framework aluminum are roughly the same as those of the hydrogen-type molecular sieve with non-framework aluminum. This specially modified molecular sieve has a higher degree of crystallinity.
[0016] In the above catalysts, preferably, the molecular sieve used includes one or a combination of two or more of Y-type molecular sieve, beta-type molecular sieve and ZSM-5 type molecular sieve; more preferably, the hydrogen-type molecular sieve is HY molecular sieve.
[0017] In the above catalyst, preferably, the mass ratio of the modified molecular sieve to alumina is 25-60:75-40; more preferably, the mass ratio of the modified molecular sieve to alumina is 35-55:65-44;
[0018] In a specific embodiment, based on the total mass of the carrier, the content of the modified molecular sieve is 30%-60%, preferably 35%-55%.
[0019] In the above catalyst, preferably, the alumina is macroporous alumina.
[0020] In the above catalyst, preferably, the hydrogenation active metal component includes Ni and Mo.
[0021] In the above catalyst, preferably, based on the total mass of the hydrocracking catalyst, the content of the hydrogenation active metal component is 15%-35%; more preferably, based on the total mass of the hydrocracking catalyst, the content of the hydrogenation active metal component is 20%-30%.
[0022] In the above catalysts, the hydrogen-type molecular sieve with non-framework aluminum can be a molecular sieve after ultra-stable hydrothermal treatment, or a molecular sieve with non-framework aluminum after chemical treatment, but is not limited thereto.
[0023] In the above catalyst, preferably, the hydrogen-type molecular sieve having non-framework aluminum is prepared by a method comprising the following steps:
[0024] The hydrogen-type molecular sieve is subjected to hydrothermal treatment to obtain the hydrothermally treated molecular sieve as a hydrogen-type molecular sieve having non-framework aluminum for subsequent dealumination treatment;
[0025] More preferably, the Na2O content of the hydrogen-type molecular sieve subjected to the hydrothermal treatment does not exceed 0.1%; in a specific embodiment, the hydrogen-type molecular sieve subjected to the hydrothermal treatment has a Na2O content of no more than 0.1% after the ammonium exchange;
[0026] More preferably, the temperature of the hydrothermal treatment is 450-900°C; further preferably, the temperature of the hydrothermal treatment is 450-800°C; further preferably, the temperature of the hydrothermal treatment is 500-700°C;
[0027] More preferably, the hydrothermal treatment time is 0.1-10 hours; further preferably, the hydrothermal treatment time is 0.5-6 hours; further preferably, the hydrothermal treatment time is 2-5 hours;
[0028] More preferably, the pressure of the hydrothermal treatment is normal pressure-0.5Mpa; further preferably, the pressure of the hydrothermal treatment is normal pressure-0.3Mpa; further preferably, the pressure of the hydrothermal treatment is 0.1-0.2Mpa;
[0029] More preferably, the hydrothermal treatment is carried out under a water vapor atmosphere; in a specific embodiment, the hydrothermal treatment is carried out under 100% water vapor conditions;
[0030] In this preferred technical scheme, an ultra-stable hydrogen-type molecular sieve having non-framework aluminum is obtained by hydrothermal treatment; then, a dicarboxylic acid having a carbon-carbon double bond and two carboxyl groups arranged on the same side of the carbon-carbon double bond and a cis structure in spatial configuration is used for dealumination treatment, and finally, the ionic non-framework aluminum is substantially completely removed while the framework aluminum and polymerized non-framework aluminum of the molecular sieve are substantially not destroyed, thereby obtaining a special modified molecular sieve as a carrier component of a hydrocracking catalyst.
[0031] In the above catalysts, preferably, the organic dicarboxylic acid solution is a maleic acid solution.
[0032] In the above catalyst, the organic dicarboxylic acid solution can be obtained by dissolving an organic dicarboxylic acid in water, or by dissolving an anhydride of an organic dicarboxylic acid in water; in one specific embodiment, the organic dicarboxylic acid solution is obtained by dissolving maleic acid in water; in another specific embodiment, the organic dicarboxylic acid solution is obtained by dissolving maleic anhydride in water.
[0033] In the above catalyst, preferably, the temperature of the dealumination treatment is 50-120°C; more preferably, the temperature of the dealumination treatment is 50-100°C; further preferably, the temperature of the dealumination treatment is 60-195°C.
[0034] In the above catalyst, preferably, the time of the dealumination treatment is 0.1-6 hours; more preferably, the time of the dealumination treatment is 0.5-3 hours.
[0035] In the above catalyst, preferably, based on the volume of the organic dicarboxylic acid solution, the molar concentration of the organic dicarboxylic acid in the organic dicarboxylic acid solution is 0.01-2 mol / L; more preferably, based on the volume of the organic dicarboxylic acid solution, the molar concentration of the organic dicarboxylic acid in the organic dicarboxylic acid solution is 0.5-1.5 mol / L.
[0036] In the above catalyst, preferably, the mass ratio of the organic dicarboxylic acid solution to the hydrogen-type molecular sieve having non-framework aluminum is 2:1-30:1; more preferably, the mass ratio of the organic dicarboxylic acid solution to the hydrogen-type molecular sieve having non-framework aluminum is 5:1-20:1.
[0037] In a specific embodiment, the dealumination treatment of the hydrogen-type molecular sieve having non-framework aluminum using an organic dicarboxylic acid solution is achieved by the following method:
[0038] The hydrogen-type molecular sieve with non-framework aluminum is mixed with an organic dicarboxylic acid solution and is subjected to dealumination treatment under stirring conditions.
[0039] In the above catalyst, preferably, the washing can be performed with water; in a specific embodiment, the water washing temperature is 60-90° C., and the number of water washings is 3-5 times.
[0040] In the above catalyst, preferably, the drying temperature is 100-160°C; more preferably, the drying temperature is 110-130°C.
[0041] In the above catalyst, preferably, the drying time is 30-300 minutes; more preferably, the drying time is 60-180 minutes.
[0042] In the above catalyst, preferably, the modified molecular sieve is a modified Y molecular sieve;
[0043] More preferably, the unit cell parameter of the modified Y molecular sieve is 2.4281-2.4493 nm; further preferably, the unit cell parameter of the modified Y molecular sieve used is 2.4282-2.4490 nm;
[0044] More preferably, the modified Y molecular sieve has a relative crystallinity of 100%-130%; further preferably, the modified Y molecular sieve has a relative crystallinity of 100%-130%;
[0045] More preferably, the modified Y molecular sieve has a silicon-aluminum atomic ratio of 5-30; further preferably, the modified Y molecular sieve has a silicon-aluminum atomic ratio of 6-28.
[0046] More preferably, the B acid content of the modified Y molecular sieve accounts for more than 90% of the total acid content; further preferably, the B acid content of the modified Y molecular sieve accounts for more than 92% of the total acid content.
[0047] In the above catalyst, preferably, the pore size of the modified Y molecular sieve is 14-23 nm.
[0048] The present invention also provides a method for preparing the above hydrocracking catalyst, wherein the method comprises:
[0049] Carrier preparation step: kneading the modified Y-type molecular sieve and alumina into a mixed shape, drying and calcining to obtain the catalyst carrier;
[0050] Active component loading step: impregnating a hydrogen active metal component precursor solution on the carrier, and obtaining the hydrocracking catalyst through drying and calcining.
[0051] In the above preparation method, preferably, in the carrier preparation step, the drying temperature is 90-120°C.
[0052] In the above preparation method, preferably, in the carrier preparation step, the drying time is 3-8 hours.
[0053] In the above preparation method, preferably, in the carrier preparation step, the calcination temperature is 500-600°C.
[0054] In the above preparation method, preferably, in the carrier preparation step, the calcination time is 3-8 hours.
[0055] In the above preparation method, preferably, in the active component loading step, the drying temperature is 90-120°C.
[0056] In the above preparation method, preferably, in the active component loading step, the drying time is 3-8 hours.
[0057] In the above preparation method, preferably, in the active component loading step, the calcination temperature is 500-600°C.
[0058] In the above preparation method, preferably, in the active component loading step, the calcination time is 3-8 hours.
[0059] In the above preparation method, preferably, the hydrogen-active metal component precursor is a salt and / or oxide of the hydrogen-active metal component.
[0060] The present invention also provides the above hydrocracking catalyst in diesel fuel Application of hydrocracking catalysis in the preparation of naphtha.
[0061] The technical solution provided by the present invention is to modify the HY molecular sieve with non-framework aluminum by using an organic dicarboxylic acid with two carboxyl groups in a cis-structure as a dealuminizing agent to obtain a specially modified Y molecular sieve, and then use this specially modified molecular sieve to form a carrier in combination with alumina, and then load the hydrogenation active component on the carrier to form the hydrocracking catalyst of the present invention. This hydrocracking catalyst can effectively achieve high-yield high-aromatic potential naphtha.
[0062] The specially modified Y molecular sieve used in the technical solution of the present invention is acid-modified using a dicarboxylic acid with a special structure. The dicarboxylic acid with a special structure can form a cyclic transition state with ionic non-framework aluminum by virtue of its own characteristic of having two carboxyl groups in a homeotropic state in the molecular spatial configuration to promote the removal of non-framework aluminum. Under mild reaction conditions, selective complexation removal of ionic non-framework aluminum can be achieved without affecting framework aluminum and polymeric non-framework aluminum. The specially modified Y molecular sieve used in the technical solution of the present invention contains almost no ionic non-framework aluminum, and its framework aluminum and polymeric non-framework aluminum are roughly the same as those of a hydrogen-type molecular sieve with non-framework aluminum, and has a higher degree of crystallinity.
[0063] The effect of maintaining high crystallinity of molecular sieve while achieving efficient dealumination is achieved. Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0064] 1. The catalyst provided by the technical solution of the present invention adopts a Y molecular sieve modified with a special organic dicarboxylic acid as a cracking active component. The modified molecular sieve has unobstructed pores, strong accessibility of active sites within the crystal, high utilization rate of acid sites, and high cracking selectivity.
[0065] 2. The catalyst provided by the technical solution of the present invention has the characteristics of suitable acid strength, smooth and regular pores, high cracking activity and strong selectivity. DETAILED DESCRIPTION
[0066] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the content described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0067] Example 1
[0068] This embodiment provides a hydrocracking catalyst CAT-1, which is prepared by the following method:
[0069] 200 g of HY molecular sieve with a Na2O content of 0.08% was hydrothermally treated under 100% water vapor to obtain a molecular sieve after hydrothermal treatment (a hydrogen-type molecular sieve with non-framework aluminum) and recorded as HY-STEAM-1 molecular sieve; wherein the hydrothermal treatment temperature was 500°C, the pressure was 0.1 MPa, and the time was 10 hours;
[0070] Dissolve 100 g of HY-STEAM-1 molecular sieve in 500 ml of deionized water, heat to 95°C, add 29.1 g of maleic acid, and stir for 3 hours to complete the dealumination treatment;
[0071] After the molecular sieve after dealuminization is completely filtered, it is washed with deionized water at 60°C for 1 hour, and the washing process is repeated 5 times; after the molecular sieve after water washing is filtered, it is placed in an oven at 110°C and dried for 180 minutes to obtain a modified Y molecular sieve, which is recorded as HT-Y-1 molecular sieve;
[0072] 35 g of HT-Y-1 molecular sieve dry base and 65 g of alumina dry base were placed in a kneader and mixed for 10 min, acid water was added and kneaded, dried at 120°C for 4 hours, and calcined at 550°C for 4 hours to prepare a catalyst carrier, which was recorded as S-1;
[0073] A solution containing 4wt% NiO and 16wt% MoO3 (the concentration is based on the total mass of the solution) was prepared, and equal volumes were impregnated on the S-1 carrier. The catalyst was dried at 140°C for 4 hours and calcined at 600°C for 4 hours to prepare the catalyst CAT-1.
[0074] Example 2
[0075] This embodiment provides a hydrocracking catalyst CAT-2, which is prepared by the following method:
[0076] 200 g of HY molecular sieve with a Na2O content of 0.08% was hydrothermally treated under 100% water vapor to obtain a molecular sieve after hydrothermal treatment (a hydrogen-type molecular sieve with non-framework aluminum) and recorded as HY-STEAM-2 molecular sieve; wherein the hydrothermal treatment temperature was 700°C, the pressure was 0.3 MPa, and the time was 5 hours;
[0077] Dissolve 100 g of HY-STEAM-2 molecular sieve in 1000 ml of deionized water, heat to 75°C, add 98.1 g of maleic anhydride (maleic anhydride is dissolved in deionized water to form a maleic acid solution), and stir for 1.5 hours to complete the dealumination treatment;
[0078] After the molecular sieve after dealuminization is completely filtered, it is washed with deionized water at 75°C for 1 hour, and the washing process is repeated 4 times; after the molecular sieve after water washing is filtered, it is placed in an oven at 120°C and dried for 120 minutes to obtain a modified Y molecular sieve, which is recorded as HT-Y-2 molecular sieve;
[0079] 35 g of HT-Y-2 molecular sieve dry base and 55 g of alumina dry base were placed in a kneader and mixed for 10 min, acid water was added and kneaded, dried at 90°C for 3 hours, and calcined at 500°C for 3 hours to prepare a catalyst carrier, which was recorded as S-2;
[0080] A solution containing 5wt% NiO and 20wt% MoO3 (the concentration is based on the total mass of the solution) was prepared, and equal volumes were impregnated on the S-2 carrier. The catalyst was dried at 90°C for 3 hours and calcined at 500°C for 4 hours to prepare the catalyst CAT-2.
[0081] Example 3
[0082] This embodiment provides a hydrocracking catalyst CAT-3, which is prepared by the following method:
[0083] 200 g of HY molecular sieve with a Na2O content of 0.08% was hydrothermally treated under 100% water vapor to obtain a molecular sieve after hydrothermal treatment (a hydrogen-type molecular sieve with non-framework aluminum) and recorded as HY-STEAM-3 molecular sieve; wherein the hydrothermal treatment temperature was 900°C, the pressure was 0.5 MPa, and the time was 0.1 hour;
[0084] Dissolve 100 g of HY-STEAM-3 molecular sieve in 2000 ml of deionized water, heat to 60°C, add 348.2 g of maleic acid, and stir for 0.5 hours to complete the dealumination treatment;
[0085] After the molecular sieve after dealuminization is completely filtered, it is washed with deionized water at 90°C for 1 hour, and the washing process is repeated 3 times; after the molecular sieve after water washing is filtered, it is placed in an oven at 130°C for 160 minutes to obtain a modified Y molecular sieve, which is recorded as HT-Y-3 molecular sieve;
[0086] 55 g of HT-Y-3 molecular sieve dry base and 45 g of alumina dry base were placed in a kneader and mixed for 10 min, acid water was added and kneaded, dried at 110°C for 8 hours, and calcined at 600°C for 8 hours to prepare a catalyst carrier, which was recorded as S-3;
[0087] A solution containing 8 wt% NiO and 22 wt% MoO3 (the concentration is based on the total mass of the solution) was prepared, and equal volumes were impregnated on the S-3 carrier. The catalyst was dried at 120°C for 8 hours and calcined at 600°C for 8 hours to prepare the catalyst CAT-3.
[0088] Comparative Example 1
[0089] This comparative example provides a hydrocracking catalyst CAT-4, which is prepared by the following method:
[0090] HY-STEAM-1 molecular sieve was prepared in the same manner as in Example 1;
[0091] Dissolve 100 g of HY-STEAM-1 molecular sieve in 500 ml of deionized water, heat to 95°C, add 93.1 g of EDTA disodium salt (EDTA disodium salt is dissolved in deionized water to obtain EDTA solution), and stir for 3 hours to complete the dealumination treatment;
[0092] After the dealuminized molecular sieve was completely filtered, it was washed with deionized water at 60°C for 1 hour, and the washing process was repeated 5 times; after filtering the washed molecular sieve, it was placed in an oven at 110°C for 180 minutes to obtain a modified Y molecular sieve, which was recorded as HT-Y-4 molecular sieve.
[0093] 55 g of HT-Y-4 molecular sieve dry base and 45 g of alumina dry base were placed in a kneader and mixed for 10 min, acid water was added and kneaded, dried at 120°C for 4 hours, and calcined at 550°C for 4 hours to prepare a catalyst carrier, which was recorded as S-4;
[0094] A solution containing 8 wt% NiO and 22 wt% MoO3 (the concentration is based on the total mass of the solution) was prepared, and equal volumes were impregnated on the S-4 carrier. The catalyst CAT-4 was prepared after drying at 140°C for 4 hours and calcining at 600°C for 4 hours.
[0095] Comparative Example 2
[0096] This comparative example provides a hydrocracking catalyst CAT-5, which is prepared by the following method:
[0097] HY-STEAM-1 molecular sieve was prepared in the same manner as in Example 1;
[0098] 55 g of HY-STEAM-1 molecular sieve dry base and 45 g of alumina dry base were placed in a kneader and mixed for 10 min, acid water was added and kneaded, dried at 120°C for 4 hours, and calcined at 550°C for 4 hours to prepare a catalyst carrier, which was recorded as S-5;
[0099] A solution containing 8 wt% NiO and 22 wt% MoO3 (the concentration is based on the total mass of the solution) was prepared, and equal volumes were impregnated on the S-5 carrier. The catalyst was dried at 140°C for 4 hours and calcined at 600°C for 4 hours to prepare the catalyst CAT-5.
[0100] Experimental Example 1
[0101] The crystallinity, specific surface area, pore volume and pore size of the HY-STEAM-1 molecular sieve, HT-Y-1 molecular sieve, HT-Y-2 molecular sieve, HT-Y-3 molecular sieve and HT-Y-4 molecular sieve in Examples 1 to 3 and Comparative Example 1 were tested respectively, and the results are shown in Table 1.
[0102] Table 1 Properties of molecular sieves before and after modification with different organic acids
[0103]
[0104] As can be seen from Table 1, the relative crystallinity of the molecular sieve modified by maleic acid solution is significantly increased, and the mesopore volume and specific surface area are also improved to a certain extent. Therefore, the molecular sieve modified by maleic acid solution has appropriate acid strength and smooth and regular pores.
[0105] Experimental Example 2
[0106] Hydrocatalytic cracking tests were carried out using the CAT-1 catalyst, CAT-2 catalyst, CAT-3 catalyst, CAT-4 catalyst, and CAT-5 catalyst provided in Examples 1 to 3, Comparative Example 1, and Comparative Example 2, respectively.
[0107] The catalyst performance evaluation was carried out using a one-stage cascade hydrocracking process on a 100ml small-scale high-pressure hydrogenation unit in the laboratory. The first reactor was filled with pre-refined catalyst, and the nitrogen content of the first product oil was controlled to be less than 10ppm; the second reactor was filled with the catalyst to be evaluated; the catalyst loading in the first reactor and the second reactor was 25ml, and the catalyst in the first reactor and the second reactor was broken into strips of 3-8mm and diluted with alumina carrier calcined at a ratio of 1:2. The temperature of the first reactor was 365°C, and the volume space velocity in the first reactor was 1.5h -1 The temperature of the second reactor was 375°C and the volume space velocity in the first reactor was 2.0 h -1 ; The pressure of the hydrogenation unit is 10Mpa; The properties of the raw oil used in the hydrocatalytic cracking test are shown in Table 2. The results are shown in Table 3:
[0108] Table 2 Evaluation oil properties
[0109]
[0110] Table 3 Distribution and properties of hydrocracking products
[0111]
[0112]
[0113] As can be seen from Table 3, from CAT-1 to CAT-3, as the molecular sieve content increases, the heavy naphtha yield gradually increases, benefiting from the relatively smooth channels of the molecular sieve, the heavy naphtha aromatic potential is high, and the hydrocracking diesel cetane index also gradually increases. Compared with CAT-3, CAT-4 and CAT-5 have significantly lower heavy naphtha yields than CAT-3 under the premise of the same molecular sieve addition amount, and the light naphtha yield is higher, indicating that the molecular sieve hydrocracking activity and selectivity after treatment by the present invention are improved.
[0114] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A hydrocracking catalyst, wherein: The catalyst comprises a hydrogenation active metal component and a carrier, wherein the carrier comprises a modified molecular sieve and alumina; wherein: The modified molecular sieve is prepared by a method comprising the following steps: The hydrogen-type molecular sieve is subjected to hydrothermal treatment to obtain a hydrogen-type molecular sieve having non-framework aluminum for subsequent dealumination treatment; wherein the temperature of the hydrothermal treatment is 450-900° C., the time of the hydrothermal treatment is 0.1-10 hours, the pressure of the hydrothermal treatment is normal pressure-0.5 MPa, and the hydrothermal treatment is carried out under a water vapor atmosphere; At 50-120° C., a hydrogen-type molecular sieve having non-framework aluminum is dealuminated using an organic dicarboxylic acid solution; wherein the organic dicarboxylic acid in the organic dicarboxylic acid solution contains a carbon-carbon double bond and two carboxyl groups are arranged on the same side of the carbon-carbon double bond, and has a cis structure in terms of spatial configuration; wherein the molar concentration of the organic dicarboxylic acid in the organic dicarboxylic acid solution is 0.01-2 mol / L based on the volume of the organic dicarboxylic acid solution; The molecular sieve after dealuminization is washed and dried to obtain a modified molecular sieve; The molecular sieves used include one or a combination of two or more of Y-type molecular sieves, beta-type molecular sieves and ZSM-5-type molecular sieves.
2. The catalyst according to claim 1, wherein The hydrogen type molecular sieve uses HY molecular sieve.
3. The catalyst according to claim 2, wherein The unit cell parameters of the modified Y molecular sieve are 2.4281-2.4493 nm.
4. The catalyst according to claim 2, wherein The unit cell parameters of the modified Y molecular sieve are 2.4282-2.4490 nm.
5. The catalyst according to claim 2, wherein The silicon-aluminum atomic ratio of the modified Y molecular sieve is 5-30.
6. The catalyst according to claim 2, wherein The silicon-aluminum atomic ratio of the modified Y molecular sieve is 6-28.
7. The catalyst according to claim 1, wherein Based on the total mass of the hydrocracking catalyst, the content of the hydrogenation active metal component is 15%-35%.
8. The catalyst according to claim 1, wherein Based on the total mass of the hydrocracking catalyst, the content of the hydrogenation active metal component is 20%-30%.
9. The catalyst according to any one of claims 1, 7 and 8, wherein The mass ratio of the modified molecular sieve to alumina is 25-60:75-40.
10. The catalyst according to any one of claims 1, 7 and 8, wherein The mass ratio of the modified molecular sieve to alumina is 35-55:65-44.
11. The catalyst according to any one of claims 1, 7 and 8, wherein The hydrogenation active metal component includes Ni and Mo.
12. The catalyst according to claim 1, wherein The Na2O content of the hydrogen-type molecular sieve subjected to the hydrothermal treatment does not exceed 0.1%.
13. The catalyst according to claim 1, wherein The temperature of the hydrothermal treatment is 450-800°C.
14. The catalyst according to claim 1, wherein The temperature of the hydrothermal treatment is 500-700°C.
15. The catalyst according to claim 1, wherein The time of the hydrothermal treatment is 0.5-6 hours.
16. The catalyst according to claim 1, wherein The hydrothermal treatment time is 2-5 hours.
17. The catalyst according to claim 1, wherein The pressure of the hydrothermal treatment is normal pressure-0.3 MPa.
18. The catalyst according to claim 1, wherein The pressure of the hydrothermal treatment is normal pressure-0.2Mpa.
19. The catalyst according to claim 1, wherein The organic dicarboxylic acid solution is a maleic acid solution.
20. The catalyst according to claim 1 or 19, wherein Based on the volume of the organic dicarboxylic acid solution, the molar concentration of the organic dicarboxylic acid in the organic dicarboxylic acid solution is 0.5-1.5 mol / L.
21. The catalyst according to claim 1 or 17, wherein The mass ratio of the organic dicarboxylic acid solution to the hydrogen-type molecular sieve having non-framework aluminum is 2:1-30:
1.
22. The catalyst according to claim 1 or 17, wherein The mass ratio of the organic dicarboxylic acid solution to the hydrogen-type molecular sieve having non-framework aluminum is 5:1-20:
1.
23. The catalyst according to claim 1, wherein The temperature of the dealumination treatment is 50-100°C.
24. The catalyst according to claim 1, wherein The temperature of the dealumination treatment is 60-95°C.
25. The catalyst according to claim 1, wherein The dealumination treatment time is 0.1-6 hours.
26. The catalyst according to claim 1, wherein The dealumination treatment time is 0.5-3 hours.
27. The method for preparing the hydrocracking catalyst according to any one of claims 1 to 26, wherein: The method includes: Carrier preparation step: kneading the modified molecular sieve and alumina into a mixture, drying and calcining to obtain the catalyst carrier; Active component loading step: impregnating a hydrogenation active metal component precursor solution on the carrier, and obtaining the hydrocracking catalyst through drying and calcining.
28. The preparation method according to claim 27, wherein In the carrier preparation step, the drying temperature is 80-160°C.
29. The preparation method according to claim 27, wherein: In the carrier preparation step, the drying time is 2-10 hours.
30. The preparation method according to claim 27, wherein: In the carrier preparation step, the calcination temperature is 450-650°C.
31. The preparation method according to claim 27, wherein In the carrier preparation step, the calcination time is 2-10 hours.
32. The preparation method according to claim 27, wherein: In the active component loading step, the drying temperature is 80-160°C.
33. The preparation method according to claim 27, wherein: In the active component loading step, the drying time is 2-10 hours.
34. The preparation method according to claim 27, wherein In the active component loading step, the calcination temperature is 400-600°C.
35. The preparation method according to claim 27, wherein In the active component loading step, the calcination time is 2-10 hours.
36. The preparation method according to claim 27, wherein The hydrogenation active metal component precursor is a salt and / or oxide of the hydrogenation active metal component.
37. Use of the hydrocracking catalyst according to any one of claims 1 to 26 in the catalytic preparation of naphtha by diesel hydrocracking.
Citation Information
Patent Citations
Preparation of hydrogenation catalyst
CN101172260A
Method for modifying mesoporous-rich USY (Ultra-Stable Y) molecular sieve in combined manner
CN104229823A
Hydrocracking catalyst and preparation method thereof
CN105709798A
Preparation method for chemical hydrocracking catalyst
CN105709801A
Hydrocracking catalyst containing Y molecular sieve and preparation method thereof
CN101450320A